Przejęcia i fuzje jako proces zmian w przedsiębiorstwie - Zając, Czesław (Mergers and Acquisitions as Processes of Changes in a Company, 2009)
Mergers and acquisitions (M&A) are an example of multidimensional and complex processes of changes which generate at the same time many other changes in all key fields of acquired or joining companies. In spite of different approaches presented in the publications we can distinguish three typical phases of each M&A process, i.e.: preparation, introduction and freezing of the ownership change. Every phase includes typical and non-typical tasks because of the specific context of the ownership change. The results of research indicate an organizational and social integration as one of the most important factors of success of the ownership change. Appropriate recognition and effective solving of organizational and social problems occurring in the process of M&A strongly support such integration. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 144-150